PENGARUH SARANA PRASARANA PENDIDIKAN DAN KUALITAS GURU TERHADAP PRESTASI BELAJAR SISWA SMAK TARUNA JAYA SAMPIT - Munde, Lusia (Jurnal Aplikasi Manajemen Pendidikan, 2015)
This study aims to determine whether there is influence of education infrastructure and quality of teachers on learning achievement obtained SMAK Taruna Jaya Sampit.                This research is a quantitative analysis. Relationship variables in the study is a causal relationship (causal). The independent variable in this study, the effect of educational infrastructure (X1), the quality of teachers (X2) and the dependent variable was student achievement (Y). The study population was SMAK Taruna Jaya Sampit 2014/2015 school year as much as 167 person .Sampel were taken by 5 classes, namely class X1, X2, X3, XI, XI IPS. Data obtained by using questionnaires and student achievement in the second semester 2014/2015.                 There is also the results of hypothesis testing by t test that a significant level of infrastructure (X 1) 0,000 0,050 ≤ infrastructure which means variable effect on student achievement variable (Y) is thus HA Ho rejected and received the first hypothesis is accepted. For the quality of teachers (X2) 0.000 ≤ 0.050, which means the variable quality of teachers (X2) effect on student achievement (Y) is thus HA Ho rejected and receive the second hypothesis is accepted. By obtaining the calculated F value of 46.427 and probability of 0.000 <0.05 there is influence between infrastructure (X1) and the quality of teachers (X2) simultaneously on student achievement thus a third hypothesis is accepted.                Data were analyzed with multiple linear regression. Obtained regression equation is Y = 42.453 + (0.261) X1 + (0.436) X2. The results showed that the infrastructure and the quality of the teacher effect on student achievement SMAK Taruna Jaya Sampit with the contribution of 44.7% while the remaining 55.3% by other variables not examined in this study.